The Resurgence of Informal Settlements in Cuidad Juarez: Estrella Sol del Poniente, Causes and Conditions - Tajudeen Oluwafemi Noibi; Ramon Leopoldo Moreno Murrieta; Digvijay Pandey (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
The growth of informal settlements in the city of Cuidad Juarez has been part of the historical development of urbanization of the city. The sporadic rise in the disturbing trend was later grounded to a halt by the agencies of government across the 3 tiers, namely, municipal, state, and federal. Outstandingly, the growth of the city of Cuidad Juarez and the existence of slums were largely pronounced by location and the neoliberalist ideology of the commodification of human needs. The rise of an informal settlement in recent times in the city, namely Estralla Sol del Poniente was basically due to the population growth in irregular settlements otherwise known as colonial which have prompted those living in precarious conditions to re-establish a habitat of their own. The living conditions of characterizing a slum are poor public services such as water supply, sanitation, lack of electricity, among others. Through the methodology of qualitative research, the ethnography findings suggest that lack of trust in government agencies which also have reinforced social exclusion has further justified the construction of informal settlements. There is the need for the municipal authority of the border city to understand that the ripple effects of the immediate past have raised its ugly repercussions. The need to subjectively understand policies the effectiveness of land policies and all-inclusive urban housing, skill acquisition, and firm legislative and executive policy implementation would further control the rise of slums.